2016
DOI: 10.1136/bmjopen-2015-010152
|View full text |Cite
|
Sign up to set email alerts
|

Disability pension due to common mental disorders and subsequent suicidal behaviour: a population-based prospective cohort study

Abstract: ObjectiveAdverse health outcomes, including suicide, in individuals on disability pension (DP) due to mental diagnoses have been reported. However, scientific knowledge on possible risk factors for suicidal behaviour (suicide attempt and suicide) in this group, such as age, gender, underlying DP diagnoses, comorbidity and DP duration and grade, is surprisingly sparse. This study aimed to investigate associations of different measures (main and secondary diagnoses, duration and grade) of DP due to common mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 50 publications
0
17
0
2
Order By: Relevance
“…CMD was defined as ‘depressive episode’ (F32), ‘recurrent depressive disorder’ (F33), ‘phobic anxiety disorder’ (F40), ‘other anxiety disorder’ (F41), ‘obsessive-compulsive disorder’ (F42), and ‘reaction to severe stress and adjustment disorder’ (F43) [21–24], based on the corresponding codes of the International Classification of Diseases (ICD) version 10 [25]. …”
Section: Methodsmentioning
confidence: 99%
“…CMD was defined as ‘depressive episode’ (F32), ‘recurrent depressive disorder’ (F33), ‘phobic anxiety disorder’ (F40), ‘other anxiety disorder’ (F41), ‘obsessive-compulsive disorder’ (F42), and ‘reaction to severe stress and adjustment disorder’ (F43) [21–24], based on the corresponding codes of the International Classification of Diseases (ICD) version 10 [25]. …”
Section: Methodsmentioning
confidence: 99%
“…Depression and low self-rated health are risk factors for longer sick leave periods (Nielsen et al, 2012) and only 20% of people who have been on sick leave for at least six months will return to work in the following five years. Further, long periods of sick leave may itself affect a person's health, wellbeing and access to the labour market negatively (Rahman, Alexanderson, Jokinen, & Mittendorfer-Rutz, 2016;Vingard, Alexanderson, & Norlund, 2004).…”
Section: Amplitude and Consequencesmentioning
confidence: 99%
“…Several studies have shown associations between mental disorders and SA [21,22,24], that in turn is a risk factor for suicidal behavior [25][26][27]. A number of studies have shown that DP, due to mental disorders, is associated with both suicide attempt and suicide [28][29][30]. Moreover, DP has been demonstrated as a strong risk indicator for suicidal behavior among certain groups, including multiple sclerosis (MS) [31].…”
Section: Introductionmentioning
confidence: 99%